HUBUNGAN BERAT BADAN BAYI LAHIR DAN ANEMIA DALAM KEHAMILAN DENGAN KEJADIAN PENDARAHAN POST PARTUM - Afrika, Eka; Rizki, Merisa (JOURNAL OF MIDWIFERY SCIENCE, 2021)
Background :Post partum bleeding is blood loss that exceeds 500 ml, which occurs after the baby is born in vaginal delivery and exceeds 1000 ml at cesarean section, or bleeding that is more than normal and has caused changes in vital signs.Objective:This study aims to determine the relationship between birth weight, anemia in pregnancy and prolonged labor with the incidence of postpartum hemorrhage in pregnant women. Methods:The research design used is the Analytical Survey method with a case control approach, namely research by comparing the case group and control group based on their exposure status.Results:Based on the results of the Chi Square test, a p-value of 0.002 (p-value = 0.05) was obtained, which means that there was a significant relationship between birth weight and postpartum hemorrhage. 05) which means that there is a significant relationship between anemia in pregnancy and postpartum hemo. Conclusion: There is a relationship between birth weight, anemia in pregnancy and prolonged labor with the incidence of postpartum hemorrhage Keywords: Birth weight, anemia and post partum haemorrhage